APLIKASI PENGGUNAAN SISTEM KANTONG PADA BUDIDAYA RUMPUT LAUT SEBAGAI PENGGERAK PEREKONOMIAN MASA PANDEMI MASYARAKAT PESISIR - Dewi, A.P.W.K.; Restu, I.W.; Julyantoro, P.G.S.; Kartika, G.R.A.; Ernawati, N.M. (Buletin Udayana Mengabdi; Vol 23 No 5 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i05.p08, 2023)
The waters of Gunung Payung in Kutuh Village have the potential to become a location for seaweed cultivation development. One of the seaweed cultivation developments that can be applied as an economic driver during the pandemic is the use of bag systems in seaweed cultivation. The method used in this activity is to provide assistance in applying the bag system to seaweed cultivation in Gunung Payung Waters. BUMDA Kutuh was involved too as a partner in this activity. Community representatives of seaweed cultivation group members participated in the socialization held at Gunung Payung Beach Hall and practiced bag making directly. The seaweed bags were made from 12inch pipes with a size of 1.5 m x 1m x 0.5 m, where 1 large bag consisted of 3 small bags measuring 0.5 m x 1m x 0.5m. The number of bags made was six. Each bag contained as much as 500 grams of seaweed seedlings, which were then put into the bag without tying. After the bags were ready for use, the installation and planting of seaweed seedlings were carried out at the lowest tide, around 16.00 WITA, in the waters of Gunung Payung. The conclusion of this service activity is that the community welcomes the service activities and is enthusiastic about participating in the training activities, as can be seen from the interaction of the participants during the activity. Keywords: Seaweed Cultivation, Gunung Payung, Bag system